REQUIREMENTS FOR TRANSPORT MANAGER'S PROFESSIONAL COMPETENCE - Hvizdakova, Zuzana (Doprava a spoje, 2012)
Article "Requirements for Transport Manager's Professional Competence" deals with professional competence of transport managers problems. Professional competence of transport manager in road transport is regulated by Regulation (EC) No 1071/2009. For professional competence obtaining it is important to pass the exam. According to this regulation Member States can organise the exam in different ways. Article describes conditions for professional competence obtaining in different Member States especially differences between them like mandatory oral exam, duration of written and oral exam, training for applicators prior to the exam or exemption from exam. In this article were analysed differences between Slovakia, Hungary, Sweden, Ireland, Czech and Austria.